2009
DOI: 10.1007/978-3-642-01757-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Histogram Pair Based Image Lossless Data Embedding

Abstract: Abstract. This paper presents an optimum histogram pair based image reversible data hiding scheme using integer wavelet transform and adaptive histogram modification. This new scheme is characterized by (1) the selection of best threshold T , which leads to the highest PSNR of marked image for a given payload; (2) the adaptive histogram modification, which aims at avoiding underflow and/or overflow, is carried out only when it is necessary, and treats the left side and right side of histogram individually, see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 9 publications
0
60
2
Order By: Relevance
“…Table 1 Considering the GAP is the best predictor of all, we now compare the performance of the ASPE with the GAP predictor against the well known high capacity data hiding schemes reported in the literature, such as [5], [7], [10], [11], [12], [13], and [18]. One of the main features of our scheme is that the quality of marked image is impaired proportional to the required capacity.…”
Section: Experimental Results and Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 Considering the GAP is the best predictor of all, we now compare the performance of the ASPE with the GAP predictor against the well known high capacity data hiding schemes reported in the literature, such as [5], [7], [10], [11], [12], [13], and [18]. One of the main features of our scheme is that the quality of marked image is impaired proportional to the required capacity.…”
Section: Experimental Results and Evaluationsmentioning
confidence: 99%
“…Following the methods of LSB, difference-expansion and vector quantization algorithm groups, the last category of data hiding reported in [10], [11], [12], [13] and [14] which have attracted great interests in recent years began by the work of Ni et al [10]. The main idea in this category is to use distribution of numbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, distortion is caused by both expansion and shifting. In the case of histogram shifting, an optimal approach is proposed by Hwang and others [17] and Xuan and others [20]. In general, probability distribution of the prediction error is Laplacian and exponentially decreases from the center of the histogram.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lin and Hsueh [13] suggested a lossless scheme based on increasing the differences between two adjacent pixels. Among the studies performed on transform domain Xuan et al [14] reported the remarkable reversible method carried out in the integer wavelet transform domain.…”
Section: Introductionmentioning
confidence: 99%